Assessing the added value of the recent declaration on unregulated fishing for sustainable governance of the central Arctic Ocean. (April 2016) - Shephard, Grace Elizabeth; Dalen, Kari; Peldszus, Regina; Aparício, Sara; Beumer, Larissa; Birkeland, Roger; Gkikas, Nikolaos; Kourantidou, Melina; Ktenas, Panagiotis; Linde, Peter Wilhelm; Marazzi, Francesco; Pincinato, Ruth Beatriz Mezzalira; et al.
Abstract: The 'Declaration concerning the prevention of unregulated high seas fishing in the central Arctic Ocean' signed by the Arctic 5 nations, limits unregulated high seas fishing in the central part of the Arctic Ocean, and holds potential social, economic and political impacts for numerous stakeholders. In this paper, the four Interim Measures in the Declaration are discussed and what value these measures bring beyond the existing international agreements is explored. It is found that even though the Declaration fills a gap in the management of potential fish stocks in the central Arctic Ocean, adopts an appropriate precautionary approach and encourages joint research activities, there are both opportunities and challenges connected to its implementation. The most valuable and urgent Interim Measure is that of joint scientific cooperation, which will facilitate more region-specific research and an increased understanding of the fisheries as well as the broader Arctic environment. Furthermore, the research generated by this measure will provide an important decision base for both regulation and management of human activity in the Arctic. Graphical abstract: Highlights: Discussion of Declaration on unregulated fishing in the central Arctic Ocean. Declaration fills a policy gap of potential fish stocks but not regulation. Precautionary approach underpins four interim measures. Joint research program measure most imperative for effective implementation.